MARKET-BASED STRATEGY AND COMPETITIVE GROWTH OF SMES: EVIDENCE FROM WEST JAVA, INDONESIA - Rahmi Nurfia Jamal; Fadilan Kusuma Bangsa; Ziad Sallum Atmanagara (FEBI UIN Sunan Gunung Djati Bandung, 2026)
This study examined the role of market-based strategy in driving the competitive growth of Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia. A quantitative approach was employed using a cross-sectional survey of 91 MSMEs, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that market orientation, competitive intensity, and technological dynamism significantly influenced the adoption of market-based strategy. Among these factors, market orientation emerged as the most dominant driver. Furthermore, market-based strategy exhibited a strong positive effect on competitive growth, confirming its role as a key strategic mechanism. The findings demonstrated that the impact of market-related factors on competitive growth operates through firms’ strategic responses rather than direct effects. This study contributed to the literature by providing empirical evidence from an emerging economy context and highlighted the importance of strengthening market-based strategic capabilities to achieve sustainable competitive growth among MSMEs.